Evolution and Spatiotemporal Dynamics of Enterovirus A71 Subgenogroups in Vietnam. (23rd September 2017) - Thao, Nguyen Thi Thanh; Donato, Celeste; Trang, Vu Thi Huyen; Kien, Nguyen Trung; Trang, Phạm Mai Thuy; Khanh, Tran Quoc; Nguyet, Dang Thi; Sessions, October M; Cuong, Hoang Quoc; Lan, Phan Trong; Huong, Vu Thi Que; van Doorn, H Rogier; et al.
Abstract : Southeast Asia, and Vietnam in particular, experience a significant burden of enterovirus A71 disease, with frequent outbreaks reported. This study reveals the endemicity, importation, and exportation of strains within the region informing public health measures and vaccination strategies. Abstract: Background: Enterovirus A71 (EV-A71) is the major cause of severe hand, foot, and mouth disease and viral encephalitis in children across the Asia-Pacific region, including in Vietnam, which has experienced a high burden of disease in recent years. Multiple subgenogroups (C1, C4, C5, and B5) concurrently circulate in the region with a large variation in epidemic severity. The relative differences in their evolution and epidemiology were examined within Vietnam and globally. Methods: A total of 752 VP1 gene sequences were analyzed (413 generated in this study combined with 339 obtained from GenBank), collected from patients in 36 provinces in Vietnam during 2003–2013, along with epidemiological metadata. Globally representative VP1 gene datasets of subgenogroups were used to coestimate time-resolved phylogenies and relative genetic diversity to infer virus origins and regional transmission network. Results: Despite frequent virus migration between countries, the highest genetic diversity of individual subgenogroups was maintained independently for several years in specific Asian countries representing genogroup-specific sources of EV-A71 diversity. Conclusion: This study highlights a persistent transmission network of EV-A71, with specific Asian countries seeding other countries in the region and beyond, emphasizing the need for improved EV-A71 surveillance and detailed genetic and antigenic characterization.